Kashf al-NiqÄb â€˜an Ramz al-MuqÄwamah al-ThaqÄfÄ«yah: á¹¢irÄâ€™ bayn al-MuslimÄ«n wa al-NubalÄâ€™ fÄ« Risalatay DÄrmÅ«gandul wa GÄtÅ«lÅ«shÅ« - Ali, Mochamad (Center for Study of Islam and Society (PPIM) Syarif Hidayatullah State Islamic University, 2002)
The discussion of this article is devoted to delineating the differences and even conflicting characteristics between these two sorts of the Japanese literature. Embedded within the two mentioned social and cultural groups of the Javanese, the priyayi and the santri, the two Javanese literature presented the discourses which are not only different but also disagreement between each other. In the nineteenth century Java, and also the Indonesian archipelago at large, due to the Dutcb colonial government, these mentioned two social and cultural of the Javanese developed into respectively distinct and even conflicting groups.DOI:Â 10.15408/sdi.v9i3.662